Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s00253-020-10795-6
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Hg and soil microbes: microbial diversity and mechanisms, with an emphasis on fungal processes

Abstract: Mercury (Hg) is a highly toxic metal with no known biological function, and it can be highly bioavailable in terrestrial ecosystems. Although fungi are important contributors to a number of soil processes including plant nutrient uptake and decomposition, little is known about the effect of Hg on fungi. Fungi accumulate the largest amount of Hg and are the organisms capable of the highest bioaccumulation of Hg. While referring to detailed mechanisms in bacteria, this mini-review emphasizes the progress made re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 146 publications
0
3
0
Order By: Relevance
“…Actually, Hg metabolic capacity is quite widespread among bacteria and archaea lineages (Christakis et al, 2021; Priyadarshanee et al, 2022), including bioaccumulation activity. Indeed, pure culture studies have documented significant bacterial uptake and accumulation of Hg (see Dranguet, Le Faucheur, Cosio, et al, 2017; Durand et al, 2020; Giovanella et al, 2017; Kiyono et al, 2003; Sayler et al, 1975; Zhang et al, 2020), with Hg bioaccumulation in some bacteria registering in the grams per liter range (Kis et al, 2017; Zhang et al, 2020). Further, controlled studies have shown that bacterial uptake of Hg can directly contribute to oyster Hg bioaccumulation (Sayler et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, Hg metabolic capacity is quite widespread among bacteria and archaea lineages (Christakis et al, 2021; Priyadarshanee et al, 2022), including bioaccumulation activity. Indeed, pure culture studies have documented significant bacterial uptake and accumulation of Hg (see Dranguet, Le Faucheur, Cosio, et al, 2017; Durand et al, 2020; Giovanella et al, 2017; Kiyono et al, 2003; Sayler et al, 1975; Zhang et al, 2020), with Hg bioaccumulation in some bacteria registering in the grams per liter range (Kis et al, 2017; Zhang et al, 2020). Further, controlled studies have shown that bacterial uptake of Hg can directly contribute to oyster Hg bioaccumulation (Sayler et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The role of yeasts in Hg metabolism is poorly understood. A number of fungi, of which members of Yarrowia and Cryptococcus genus are among the best characterized, have been reported to tolerate Hg using different mechanisms, through their biosorption capacity, probably mediated by thiol groups on the surface of the cell, or through bioaccumulation via the sequestration of thiol-conjugated Hg to the vacuole (Brunker and Bott 1974;Wysocki and Tamás 2010), with the possible involvement of metallothioneins, phytochelatins, and other cysteine-rich proteins, as a means for SH groups to immobilize Hg in non-toxic form (Durand et al 2020). Sulfhydryl group-based immobilization is also the mechanism used by several high H 2 S producing isolates, which can co-precipitate Hg in non-toxic form as HgS (Aatif and Zakia 2011).…”
Section: Assessment Of Mercury Resistancementioning
confidence: 99%
“…A recent review stated that exposure to Hg is a threat to microbial soil functions involved in C and N cycles ( Durand et al, 2020 ). However, the majority of studies have been carried out shortly after Hg contamination (e.g., Frey and Rieder, 2013 ; Frossard et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%